Domestication of Motan (Thynnichthys thynnoides Blkr) in Cages with Different Types of Fish Meal - Mulyadi '; Usman M.Tang; Nasehah ' (Fakultas Perikanan dan Kelautan, Universitas Riau, 2014)
ABSTRACTThe research was conducted from 18 March until 16 May 2011 in Research Station of Fisheries and Marine Science Riau University. The objective of the research was to find out the suitable fish meal as long as domestication activities on the growth and survival rates of Thynnichthys thynnoides Blkr. The fish meal used in this research was shrimp pellet, snail meat, chicken intestines and vegetables. Fish were reared in the 0.5 m x 0.5 m x 0.5 cages for 60 days with stocking density of 25 fish/m3 cage. The method used in this research was completed randomized design method with four treatments and three replications. Results showed that the best absolute growth rate of 19.02 grams, daily growth rates of 2.304 % were obtained in the treatment of dried pellet combining with vegetables, while the worst performance was obtained in treatment of dried pellet combining with vegetables with growth rate of 12.39 grams and daily growth rate of 2.134 % respectively. Water quality parameters recorded in the research were water temperature, pH, dissolved oxygen and NH3 of 27 – 30 oC; 6 – 7; 4 – 4.6 ppm; 0.006 – 0.024 ppm respectively.Keywords : Domestication, Thynnichthys thynnoides Blkr, Fish meal.